English for everyone : course book. Level 1 beginner - Harding, Rachel (English teacher); Harding, Rachel (English teacher) (DK, 2024)
"[Level 1 of] complete self-study English-language course that combines easy-to-use visual learning with crystal-clear grammar explanations, practice exercises, and free audio. his new edition includes a grammar reference section and full transcripts of the listening comprehension exercises"--from page 4 of cover.